Students’ Perceptions of Bullying at Schools: A Phenomenological Study of Students’ Bullying Experiences in Their Schooling - Saira Taj; Komal Imdad; Warda Anum; Warda Anum; Javerea Rafique (Elementary Education Online, 2023)
Bullying is a widespread social phenomenon. It has been identified as a significant problem in today’s schools. This study aims to examine students’ perceptions and definitions about bullying as a witness, victim or bully. It was a phenomenological study of students’ bullying experiences in their schooling. Through 40 in-depth interviews and using the thematic method for analysis, several themes were appeared, such as: definitions of bullying according to students’ perspectives: the sub-themes were physical, verbal and emotional bullying, role of group, role of power, bullying as in fun, bullying leads to violence. Moreover, other major theme was appearances: weight and sizes. Appearances as a motive for bullying emerged as a theme that was specified by many of those interviewed. According to many participants, weight and size were the two important reasons to get bullied, Participants’ definitions of bullying were from the angle of those who are bullied, bully, and who have witnessed bullying. In addition, theme that emerged within the data included: students view on preventions in events of bullying, methods to reduce bullying in school, where bullying takes place, this could help school administration to make strategies to reduce bullying according to the students needs. The findings of the study highlight the many factors which were used by students to bully other fellow students. So, these findings will help schools and other educational institutions to format and implement different strategies to avoid bullying in their schools and make their schools a better learning place for their students.